CD56bright cytokine-induced memory-like NK cells and NK-cell engagers synergize against non-small cell lung cancer cancer-stem cells - Paola Orecchia; Maria Cristina Mingari; Martin Felices; Monica Parodi; Luca Roz; Massimo Vitale; Giulia Bertolini; Claudia Cantoni; Maria L Guevara Lopez; Ann Gebo; Stefano Persano; Josephine Maus-Conn; et al. (Journal for ImmunoTherapy of Cancer)
Background Due to their enhanced responsiveness and persistence, cytokine-induced memory-like (CIML)-natural killer (NK) cells have emerged as new immunotherapeutic tools against malignancies. However, their effects on tumor-cell spread and metastases in solid tumors remain poorly investigated. Moreover, a clear identification of the most effective CIML-NK subsets, especially in controlling cancer stem cells (CSC), is still lacking.Methods We performed combined phenotypical and functional analyses of CIML-NK cell subsets, either selected by flow-cytometry gating, or generated from sorted CD56bright/CD56dim NK cells.By co-culture experiments, we analyzed the effect of CIML-NK cells on non-small cell lung cancer (NSCLC) cell spheroids, or patient-derived xenografts (PDX), assessing changes in their CSC content, tumorigenicity, and/or tumor disseminating capability in vivo. CIML-NK cells were also infused in PDX-bearing mice to validate their effect on the CSC dissemination from the PDX to the lungs.Finally, we generated and functionally analyzed CIML-NK cells from patients with stages I/III NSCLC (n=6).Results We show that CIML-NK cells exert antitumor activity mostly through their CD56bright cell subset, which greatly expands during CIML differentiation. Compared with NK cells conventionally activated with interleukin-2, CIML-NK cells express lower levels of check-point receptors, TIGIT and TIM3, and higher effector functions against NSCLC cells from PDX, and against in vitro-generated tumor spheroids. Remarkably, CIML-NK cells also significantly reduce the CSC-containing CD133+ cell subpopulation within spheroids and PDX, and limit tumor cell tumorigenicity and ability to disseminate CSCs from primary tumors to distant sites. Sorting experiments on CIML or tumor cell subsets reveal that CD56bright cells drive most of this anti-CSC activity, and suggest that such functional advantage could be related to increased expression of LFA-1 and ICAM-1 on CD56bright cells and CSCs, respectively. We also show that the tri-specific killer cell engager (TriKE) 1615133 significantly enhances CIML-NK cell activity against CSCs. Finally, we demonstrate that CIML-NK cells, capable of killing autologous tumor cells and responding to the 1615133 TriKE, could be induced from patients with NSCLC.Conclusions Our study discloses for the first time the therapeutic potential of CIML-NK cells in controlling CSCs and metastatic spread, highlighting the role of the CD56bright subset expansion and 1615133 TriKE for optimizing CIML-NK-based therapies against metastatic tumors.